2020
DOI: 10.1002/nop2.625
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' knowledge and practices of physical restraints in intensive care units: An observational study

Abstract: Aim To investigate the knowledge and practice of physical restraints (PR) among Jordanian intensive care unit (ICU) nurses. Design A descriptive, observational design was used. Methods A convenience sampling was used to recruit participants. We examined the knowledge of PR in 301 nurses (knowledge check) and the real‐time practice of PR in 81 nurses (direct observation) in ICU. A knowledge questionnaire was used to collect data on knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
(151 reference statements)
2
9
0
Order By: Relevance
“…In this study, the main reason for the nursing staff 's non-standard restraint decisions was the lack of knowledge of alternative restraint measures. Moreover, there was a general lack of records of physical restraint among nursing staff in this study, which was consistent with the findings of Almomani et al (36). Effective and complete records of restraint are helpful for nursing staff to grasp the overall situation of elderly restraint, identify, and deal with the adverse effects of restraint in time, and provide a reference for when to terminate restraint.…”
Section: There Is Still Room For Further Improvement In the Restraint...supporting
confidence: 88%
“…In this study, the main reason for the nursing staff 's non-standard restraint decisions was the lack of knowledge of alternative restraint measures. Moreover, there was a general lack of records of physical restraint among nursing staff in this study, which was consistent with the findings of Almomani et al (36). Effective and complete records of restraint are helpful for nursing staff to grasp the overall situation of elderly restraint, identify, and deal with the adverse effects of restraint in time, and provide a reference for when to terminate restraint.…”
Section: There Is Still Room For Further Improvement In the Restraint...supporting
confidence: 88%
“…However, collecting more data on clinical experience and knowledge of both participant nurses and researchers would be helpful to further explain the findings given. Nurse expertise and education have been demonstrated as affecting physical restraint occurrence [ 17 , 43 ], as well as the validity of the qualitative data codification performed.…”
Section: Discussionmentioning
confidence: 99%
“…According to the evidence available, decisional triggers of physical restraint use have been categorised in: (a) patient-related factors, such as risks of falls or device removal, and aggressive behaviours; (b) context-related factors, such as the lack of human resources and the work environment quality [ 16 ]; and (c) nurse-related factors, regarding the education, expertise and attitudes. The inadequate education and the negative attitudes have been reported as increasing the use of physical restraints [ 17 ]. In line with this, targeted educational interventions have been documented to be effective in preventing physical restraint use [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies found correlation with either knowledge or attitudes. For instance, Almomani et al (2021) found a significant relationship between knowledge and practice of PR, while Abd Elhameed and Elemam (2020) found a positive relationship between attitudes and practice. Conversely, other studies concluded that there was no relationship between nurses' knowledge, attitude, and practice of PR (Kaya & Dogu, 2018;Khalil, Al Ghamdi, & Al Malki, 2017) Existing publications indicate that no consensus has been reached on practice issues and attitudes regarding the use of PR in ICU, or identifying the exact factors (demographic or work related) that affect PR practices.…”
Section: Differences In Knowledge Attitudes and Practices Scores Of P...mentioning
confidence: 99%
“…Studies conducted in Jordan showed that nurses applied PR with no approval by physician or patients' families (Suliman et al, 2017). Also, other studies found low knowledge, insufficient information about alternative methods, and in adequate documentation, in addition to lack of guidelines and protocols on the use of PR, which represents as a serious problem (Almomani, Khater, Qasem, & Joseph, 2021;Nasrate et al, 2017;Suliman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%